Author and authorship in scientific publications: a foucaultian approach (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study aimed to show that author and authorship have conceptual differences. Foucault was analyzed to demarcate the author's function in discourse. The methodology used bibliographic research to analyze five works by Foucault: The Order of Discourse (1996), The Order of Things (1999), What is an Author? (2006), The Archaeology of Knowledge (2008) and Discipline and Punish (2014). Other publications with a Foucaultian approach were also part of the theoretical framework. As a result, it was identified that being an author is not restricted to the act of writing, but rather occupying a place in discourse that depends on rules and social contexts.
Keywords: author; authorship; discourse; scientific publications; Paul-Michel Foucault